2020
DOI: 10.3390/medicina56100550
|View full text |Cite
|
Sign up to set email alerts
|

Hand Injuries in the Polish Silesian Paediatric Population—An Exploratory Cross-Sectional Study of Post-Traumatic X-rays

Abstract: Background and objectives: In the paediatric population, hand injuries are one of the most frequent injuries and the second most frequent area of fracture. It is estimated that hand injuries account for up to 23% of the trauma-related causes of emergency department visits. Not only are they a significant factor in health care costs, but they may also lead to detrimental and long-term consequences for the patient. The discrepancy observed between the published studies suggests a geographical variation in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…Pediatric hand fractures were regularly distributed during a 1-year period without significant differences between the different seasons, which is according to the recent literature [12,13]. No significant differences in the month of occurrence were observed for hand fractures based on location or allocated for different age groups in a retrospective cross sectional study of 1441 post-traumatic hand radiopgraphs [12]. This was also seen in a prospective survey of 161 hand fractures with a mean patients' age of 24 (range 2-76) [13].…”
Section: Discussionsupporting
confidence: 71%
“…Pediatric hand fractures were regularly distributed during a 1-year period without significant differences between the different seasons, which is according to the recent literature [12,13]. No significant differences in the month of occurrence were observed for hand fractures based on location or allocated for different age groups in a retrospective cross sectional study of 1441 post-traumatic hand radiopgraphs [12]. This was also seen in a prospective survey of 161 hand fractures with a mean patients' age of 24 (range 2-76) [13].…”
Section: Discussionsupporting
confidence: 71%
“…The literature fails to reach a consensus on which phalanx is most susceptible to fracture in adult populations, although our findings are most consistent with those of Weum et al [7][8][9] The high frequency of blunt trauma injuries in the current population may explain the high fracture rate in the proximal phalanx, considering that a relationship between blunt trauma injuries and proximal phalanx injuries has been established in pediatric literature. 18,20,21 Thus, these findings highlight the need to carefully examine the proximal phalanx for fractures in the setting of blunt trauma injuries, and future efforts may be directed at designing safety equipment that more specifically protects the proximal phalanges from blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings in a pediatric population and one prior publication in an adult population. 7,18 However, a general consensus on the digit most susceptible to fracture is lacking in adult populations. Brown 19 found the middle finger to be the most common and suggested that the frequency of fractures is proportional to the length of the digit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EM residents must possess a comprehensive understanding of normal hand anatomy, including bones, joints, soft tissues, and vasculature, to accurately identify abnormalities and pathology on radiological images [ 5 , 6 ]. Additionally, familiarity with common injury patterns, mechanisms of injury, and clinical presentations is crucial for making accurate diagnoses and providing appropriate management strategies [ 1 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%